Impact of employee development on job satisfaction and organizational commitment: person–organization fit as moderator - Jehanzeb, Khawaja; Mohanty, Jagannath (International journal of training and development, 2018)
Researchers have begun to focus on emerging markets, particularly those in Asia, because of the phenomenal growth in the size of their business sectors and a remarkable increase in their share of global business. Businesses in the developing world are now grappling with people management issues that formerly were the preserve of businesses in the West. This study aims at exploring the role of employee development in job satisfaction and organizational commitment and in particular its moderation by person–organization fit. The context is the telecommunications sector in Pakistan. The results reported show a positive impact of employee development initiatives on employee job satisfaction and later the job satisfaction has significant impact on organizational commitment. The results also revealed, however, an unfavourable relationship between employee development and organizational commitment. The relationship between job satisfaction and organizational commitment was significantly moderated by person–organization fit.